Possible applications of spatial analyses in designing the agricultural road network with particular consideration of the environmental and landscape aspects - Krupowicz, Wioleta; Sobolewska-Mikulska, Katarzyna (International Conference “Environmental Engineering”, 2017)
The development of the agricultural road network is a complex activity based on a broad range of criteria necessary to be taken into account during analyses and desk studies. The analyses and design solutions cannot be unilateral, considering only technical and economic aspects. Elements of environmental protection and management of agricultural landscape, as well as solutions in the scope of protection of soils and waters are necessary in this type of design works, and result from solutions accepted for implementation in reference to the rural areas of all Member States of the European Union. Such a multi-aspect process requires the use of tools in an environment which technologically permits the development of multi a riant solutions to a given problem, and selection of a single, most appropriate proposal. Geographic Information Systems (GIS) currently constitute such an environment. Their undeniable advantages include their analytical possibilities which can be formalised in the form of developed models of spatial analyses – creating sets of new, ready to use tools supporting the decision making process in the scope of determination of the optimal course of agricultural roads. Additional advantages are the possibility of integration of data obtained from various sources, and presentation to stakeholders (e.g. residents, farmers, local authorities, entrepreneurs, and investors) of the obtained solutions in the form of maps, almost in real time, as well as possibility of making optimum decisions with their active participation. Easier access to GIS technology and systematically growing level of awareness regarding measurable benefits from the application of this type of solutions should also be emphasised. The article presents examples of spatial analyses allowing for relatively fast obtaining of spatial information necessary for efficient design-related decision making for the purpose of improvement of the system of agricultural roads with particular consideration of environmental and landscape aspects.
Keywords: spatial analyses; agricultural road network; environmental protection